Successful transdermal allergen delivery and allergen-specific immunotherapy using biodegradable microneedle patches. (January 2018) - Kim, Ji Hye; Shin, Jung U.; Kim, Seo Hyeong; Noh, Ji Yeon; Kim, Hye Ran; Lee, Jungsoo; Chu, Howard; Jeong, Kyoung Yong; Park, Kyung Hee; Kim, Jung Dong; Kim, Hong Kee; Jeong, Do Hyeon; et al.
Abstract: Allergen-specific immunotherapy (SIT) is an effective treatment modality for allergic diseases such as atopic dermatitis (AD). However, frequent visits over a 3-year period as well as looming adverse events tend to discourage patient compliance. Therefore, a more convenient, effective, and safe method of SIT is needed. For several decades, use of microneedles has been promoted as an efficient and precise transdermal drug delivery method. In this study, we developed Dermatophagoides farinae ( D. farinae ) extract ( DfE )-loaded microneedle patches, and evaluated their safety and efficacy as a novel SIT method. After 4 weeks of patch application, efficient allergen delivery and successful induction of immune response to DfE were demonstrated in mice, with no apparent adverse events. AD-induced NC/Nga mice received microneedle immunotherapy (MNIT) (10 μg), subcutaneous immunotherapy (SCIT) (10 μg), SCIT (100 μg), or placebo. Both MNIT (10 μg) and SCIT (100 μg) treatments improved clinical and histologic manifestations of AD skin lesions, altered immunoglobulin production, dampened Th2 cellular response, and boosted Treg infiltrates, without significant side effects; whereas SCIT (10 μg) or placebo subsets failed to show any effects. Based on the favorable safety and efficacy profiles demonstrated in mice by MNIT in the current study, we believe that MNIT may serve as a new SIT modality.